THE MECHANICAL COMPONENTS WEAR LEVEL TEST USING THE THIN LAYER ACTIVATION TECHNIQUE - Silakhudin Silakhudin (Jurnal Penelitian Saintek, 2015)
This study discusses about the thin layer activation technique to test the mechanical components wear level. The results of preliminary experimental techniques are presented. The experimental results of the technique by using a motorcycle ring samples showed that the accuracy of measurement of the wear is 8 mg. This means that it will be less precise for testing the lightweight components. It will be more eligible to the component that the weight is more than 220 g. The prospect of developing the technique was also discussed; the result is that this technique would be appropriate to be developed at the DECY-13 cyclotron facility that will soon be constructed in BATAN.